Ancrene Wisse From Pastoral Literature to Vernacular Spirituality - Gunn, C. (Religion and Culture in the Middle Ages, 2007)
Provides an introduction to "Ancrene Wisse", one of the most important works in English of the thirteenth century. This book offers a fresh contextualisation which engages with the history of lay piety and vernacular spirituality in the Middle Ages. This book is innovative in that it provides an introduction to "Ancrene Wisse", one of the most important works in English of the thirteenth century. It offers a new contextualisation which engages with the history of lay piety and vernacular spirituality in the Middle Ages, thus extending analysis of the book beyond its original purpose as a guide for anchoresses. The placing of "Ancrene Wisse" within this context also allows comparisons to be made with other literature for semi-regular women, such as sermons preached to beguines - semi-religious women who formed communities in the Low Countries and France in the High Middle Ages.